2018
DOI: 10.1111/ggr.12246
|View full text |Cite
|
Sign up to set email alerts
|

GHR1 Zircon – A New Eocene Natural Reference Material for Microbeam U‐Pb Geochronology and Hf Isotopic Analysis of Zircon

Abstract: We present multitechnique U-Pb geochronology and Hf isotopic data from zircon separated from rapakivi biotite granite within the Eocene Golden Horn batholith in Washington, USA. A weighted mean of twenty-five Th-corrected 206 Pb/ 238 U zircon dates produced at two independent laboratories using chemical abrasion-isotope dilution-thermal ionisation mass spectrometry (CA-ID-TIMS) is 48.106 ± 0.023 Ma (2s analytical including tracer uncertainties, MSWD = 1.53) and is our recommended date for GHR1 zircon. Microbea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 71 publications
(112 reference statements)
0
9
0
Order By: Relevance
“…In accordance with accepted norms, individual spot ages are reported in Table 5 with 1σ uncertainties and weighted averages for individual populations, and all ages in the text are presented with 2σ uncertainties and the mean square of weighted deviates (MSWD). An example of typical SHRIMP-RG precision and accuracy can be found in Eddy et al (2019).…”
Section: Uranium (U) and Lead (Pb) Isotope Analysismentioning
confidence: 99%
“…In accordance with accepted norms, individual spot ages are reported in Table 5 with 1σ uncertainties and weighted averages for individual populations, and all ages in the text are presented with 2σ uncertainties and the mean square of weighted deviates (MSWD). An example of typical SHRIMP-RG precision and accuracy can be found in Eddy et al (2019).…”
Section: Uranium (U) and Lead (Pb) Isotope Analysismentioning
confidence: 99%
“…A suitable natural reference material should be homogeneous in both chemical and isotopic compositions at the scale of analysis. Previous studies have identified a number of natural zircons as reference materials suitable for geochronology and isotope geochemistry, including SL7 (Kinny et al ), CZ3 (Pidgeon et al ), SL13 (Claoué‐Long et al ), 91500 (Wiedenbeck et al ), Temora (Black et al ), BR266 (Stern ), GJ‐1 (Jackson et al , Morel et al ), Mud Tank (Woodhead and Hergt ), M257 (Nasdala et al ), Plešovice (Slama et al ), Sri Lanka (Gehrels et al ), OG1/OGC (Stern et al , Kemp et al ), Penglai (Li et al ), Qinghu (Li et al ), OD‐3 (Iwano et al ), M127 (Nasdala et al ), BB (Santos et al , Lana et al ), LGC‐1 (Tian et al ), GZ7/GZ8 (Nasdala et al ), LKZ‐1 (Cheong et al ) and GHR1 (Eddy et al ). However, most of them are either exhausted or have limited availability against the increasing demands of the microbeam laboratories.…”
mentioning
confidence: 99%
“…2004), GHR1 (Eddy et al . 2019), Fish Canyon Tuff (Schmitz and Bowring 2001), RAK‐17 (Webb et al . 2020) and Plešovice zircon (Sláma et al .…”
Section: Methodsmentioning
confidence: 99%